EETRP: Energy Efficient Enhancement and Trust Aware Routing Protocol for IOT Based WSNs: Enhancing energy efficiency and security in IoT-based WSNs (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Because of the headway of data and correspondence innovations, the utilization of Internet of Things (IoT) gadgets has expanded dramatically. In the advancement of IoT, wireless sensor networks (WSNs) play out an imperative part and contains minimal expense brilliant gadgets for data gathering. In any case, such brilliant gadgets have limitations as far as calculation, handling, memory and energy assets. Alongside such limitations, one of the basic difficulties for WSN is to accomplish unwavering quality with the security of sent information in a weak climate against vindictive hubs. This paper intends to foster an energy efficient and secure routing protocol (ESR) for interruption evasion in IoT dependent on WSN to build the network time frame and information trustworthiness. ETARP finds and chooses courses based on most extreme utility with causing extra expense in overhead contrasted with the normal AODV (Ad Hoc On Demand Distance Vector) routing protocol. Reenactment results show that, in contrast with recently proposed routing protocols, to be specific, AODV-EHA and LTB-AODV (Light-Weight Trust-Based Routing Protocol), the proposed ETARP can keep a similar security level while accomplishing more energy proficiency for information bundle conveyance